Assessment of the hypoxic–ischemic encephalopathy in neonates using non-invasive near-infrared spectroscopy - Huang, Lan; Ding, Haishu; Hou, Xinling; Zhou, Congle; Wang, Guangzhi; Tian, Fenghua (Physiological measurement, 2004)
This paper introduces a method of monitoring cerebral oxygenation for healthy neonates and neonates with hypoxic-ischemic encephalopathy (HIE) using near-infrared spectroscopy. The object of this study was to investigate whether or not there were differences between the HIE group and the healthy group in terms of NIRS parameters. The subjects were all term neonates, their age ranging from 2 to 18 days. The healthy group included 25 subjects while the HIE group consisted of 16 patients. A prototype NIRS instrument, which provides the data of tissue oxygenation including regional oxygen saturation (rSO2), the increment of oxyhemoglobin concentration and hemoglobin (deltaHbO2 and deltaHb) was used, and the data of rSO2 was compared with the data from the blood gas analyzer. The result shows that: (1) the mean+/-SD of rSO2 for the healthy group was 62 +/- 4% in the frontal region under the quiet sleep condition, but the mean+/-SD of rSO2 for the HIE group was 53 +/- 3%. (2) As all subjects inhaled pure oxygen in 21 min(-1) for a period of 60 s, rSO2 for the healthy group increased rapidly, with the increase in rSO2 (deltarSO2) being 7 +/- 2.3%, but the increase in rSO2 for the HIE neonates was 3 +/- 1.5%. After inhaling oxygen, deltaHbO2 and deltaHb between the two groups were also significantly different. (3) During all the experiments SpO2 was monitored, the value of SpO2 was not significantly different between the two groups. The above observations suggest that the rSO2 in quiet condition and the values of change of rSO2, HbO2 and Hb during the inhalation of oxygen may be used as the parameters to discover and assess the HIE infants.